The target of Drosophila photoreceptor synaptic transmission is a histamine-gated chloride channel encoded by ort (hclA). - Gengs, C.; Leung, H.T.; Skingsley, D.R.; Iovchev, M.I.; Yin, Z.; Semenov, E.P.; Burg, M.G.; Hardie, R.C.; Pak, W.L. (Journal of Biological Chemistry, 2002)
By screening Drosophila mutants that are potentially defective in synaptic transmission between photoreceptors and their target laminar neurons, L1/L2, (lack of electroretinogram on/off transients), we identified ort as a candidate gene encoding a histamine receptor subunit on L1/L2. We provide evidence that the ort gene corresponds to CG7411 (referred to as hclA), identified in the Drosophila genome data base, by P-element-mediated germ line rescue of the ort phenotype using cloned hclA cDNA and by showing that several ort mutants exhibit alterations in hclA regulatory or coding sequences and/or allele-dependent reductions in hclA transcript levels. Other workers have shown that hclA, when expressed in Xenopus oocytes, forms histamine-sensitive chloride channels. However, the connection between these chloride channels and photoreceptor synaptic transmission was not established. We show unequivocally that hclA-encoded channels are the channels required in photoreceptor synaptic transmission by 1) establishing the identity between hclA and ort and 2) showing that ort mutants are defective in photoreceptor synaptic transmission. Moreover, the present work shows that this function of the HCLA (ORT) protein is its native function in vivo.